Pamakyabe: Acculturation and Basic Psychological Needs Through the Lens of Adolescent Mag-Indi Aetas of Floridablanca, Pampanga - Susim, Paulino (Journal of Interdisciplinary Perspectives, 2024)
This study examined the neglect and discrimination faced by the Mag-Indi Aeta community in Florida Blanca, Pampanga, Philippines, and its impact on their mental health. It also explored the community's adaptive strategies and their implications for cultural preservation, resilience, and basic psychological needs. Using a qualitative research design and interpretative phenomenological analysis, the study investigated the lived experiences of five adolescent Mag-Indi Aetas concerning acculturation and psychological needs. The analysis revealed ten themes: Autonomy in Expression and Interaction, Autonomy in Empowerment Dynamics, Competence in Skill Utilization and Self-Esteem Enhancement, Competence in Modern and Practical Skills, Diverse Acculturation in Values, Diverse Acculturation in Behavior, Relatedness through Varied Engagement Levels, Relatedness through Diverse Emotional Interactions, Diverse Acculturation in Knowledge, and Diverse Acculturation in Cultural Identity. This research highlighted the discrimination, acculturation processes, and psychological needs of indigenous communities, advocating for inclusive and culturally sensitive programs such as self-awareness programs, Usap Tamo benches (buddy benches), IP day, and Kapatad week. These initiatives aim to improve the well-being of indigenous populations, promote cultural exchange, and eliminate discrimination and bullying.